1791 S.C. Acts 16, An Act To Amend And More Effectually Put In Force For The Time Therein Limited, The Act Entitled An Act For The Regulation Of The Militia Of This State (Dec. Session) - (:unkn) unknown (General Publisher, 1791)
That every free man of this state, liable to bear arms in any of the regiments, battalions or companies of foot in this state and who shall appear at any such regiment or battalion muster or at any muster or review ordered by his Excellency the governor, or at any company muster ordered in pursuance of this act, or by virtue of the said act of the twenty-sixth day of March 1784, not provided with a good musket and bayonet, and cartouch box capable of containing at least twelve rounds of cartridges or other sufficient gun and a good and sufficient small sword, broad sword, cutlass or hatchet, and a powder horn or flask capable of holding at least 12 rounds of powder, and a good shot bag or pouch, capable of holding twelve balls of a proper size for his gun, and with three spare flints, shall forfeit and pay for each and every such default, the sum of two dollars, or the sum of half a dollar for each article of arms or accoutrements herein before directed, to be affected and levied on such defaulter, in the manner in and by the said act directed and appointed.
--
Keywords: ARMED FORCES